Analysis using physics model to understand magnetoelectric nanorobotic structures for targeted cell manipulation. Issue 1 (10th December 2021) - Hossain, Shadeeb; Guo, Ruyan; Bhalla, Amar
Abstract: Magnetoelectric (ME) nanorobotic structures has application in targeted biological cell manipulation and optimized drug delivery. An approximate 70 nm diameter of Cobalt Ferrite- Barium Titanate, ferromagnetic core and piezoelectric shell is studied in context to its ability for nanoelectroporation in biological cell. Physics modeling is performed using COMSOL Multiphysics and quantitative analysis is used to understand the impact of applied magnetic field on the generated mechanical waves and electric pulses. The focus of this paper is to compliment relevant in vitro studies with ME nanorobots and to understand real-time changes in magnetostriction, piezoelectric and nanoelectroporation. The design of the magnetic navigation system with the relevant parameters to generate the required flux density for magnetostriction is discussed extensively. Assuming strong coupling between the core-shell, the 20 nm piezoelectric barium titanate contributes to electric pulsation that alters the membrane permeability leading to increased conductivity. This real time theoretical analysis provides scope for relevant clinical studies for engineering swarm of nm range robotic composites for targeted cell manipulation.